DEVELOPMENT OF PEDAGOGICAL COMPETENCE OF TEACHERS OF TECHNICAL UNIVERSITIES IN THE PROCESS OF LEARNING AND TEACHING ENGLISH FOR SPECIAL PURPOSES - Ibragimova, Dildora (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
In the age of modern science and technology, the demand for the specialty "English language teacher" is increasing in society. The new status of the English language teacher set the task of significantly changing the professional training of professors, updating the content and technology of linguistic education, and improving the quality of higher education. In order to effectively carry out his professional activity, an English teacher must not only have a good command of a foreign language, but also have basic professional competence in a certain area of English for specific purposes. The article reveals the problems of developing the pedagogical competencies of teachers of technical higher education institutions in the process of learning and teaching English for special purposes.